Data on the economic lifelines and environmental impacts of home-based enterprises in Nigeria: A case study of Ikot-Ekpene, Akwa-Ibom state, Nigeria - Chioma A. John-Nsa; Ugonna C. Nkwunonwo; Nkeiru H. Ezeadichie; Vincent A. Onodugo; Ndukwe E. Chiemelu; Elijah S. Ebinne (Data in Brief, 2024)
Home-based enterprises (HBEs), which involve the use of one's residence for commercial activities, have become a prominent research focus in the fields of entrepreneurship, sustainability, and environmental management. Despite this, the lack of data impairs the ability to accurately evaluate the economic merits of this rapidly growing business model relative to its environmental effects. This article, detailing data on the demographic features of HBE operators in Ikot-Ekpene, Akwa Ibom State, Nigeria, contributes to ongoing data mining efforts towards realistic framing of HBEs. The current data represent HBEs from five Ikot-Ekpene neighborhoods: Uruk-Uso, Ifuho, G.R.A, Ibiakpan Akanawan, and Ikot Ekpene Urban. The target population of the survey included operators of HBEs and residents. A total of 400 questionnaires were issued through systematic random sampling across the five neighborhoods. The entire sample yielded 330 valid responses, which underwent a descriptive statistical analysis, compiled, and presented in tables and bar charts. Analysis of the data provided insight into the rating of the economic relevance of HBEs in relation to their associated environmental impacts. These data provide helpful insights for researchers and policymakers involved in regulating and controlling activities in the urban sphere. They also serve as a reference point for more rigorous studies on environmental management and urban informality in cities.